Endonuclease G promotes hepatic mitochondrial respiration by selectively increasing mitochondrial tRNA Thr production - Xihui Xu; Rozhin Penjweini; Lóránt Székvölgyi; Zsolt Karányi; Anne-Marie Heckel; Devikala Gurusamy; Dóra Varga; Shutong Yang; Alexandra L. Brown; Wenqi Cui; Jinsung Park; Dénes Nagy; et al. (Proceedings of the National Academy of Sciences, 2025)
Mitochondrial endonuclease G (EndoG) contributes to chromosomal degradation when it is released from mitochondria during apoptosis. It is presumed to also have a mitochondrial function because EndoG deficiency causes mitochondrial dysfunction. However, the mechanism by which EndoG regulates mitochondrial function is not known. Fat accumulation in metabolic dysfunction–associated steatotic liver disease (MASLD), which is more common in men, is caused in part by mitochondrial dysfunction. EndoG expression is reduced in MASLD liver, and EndoG deficiency causes MASLD in an obesity-independent manner but only in males. EndoG promotes mitochondrial respiration by resolving mitochondrial tRNA/DNA hybrids formed during mtDNA transcription by recruiting RNA helicase DHX30 to unwind them. EndoG also cleaves off the 3′-end of the H-strand transcript that can prevent mt-tRNA Thr precursor cloverleaf-folding, and processing, which increases mt-tRNA Thr production and mitochondrial translation. Using fluorescent lifetime imaging microscopy technology to visualize oxygen consumption at the individual mitochondrion level, we found that EndoG deficiency leads to the selective loss of a mitochondrial subpopulation with high-oxygen consumption. This defect was reversed with mt-tRNA Thr supplementation. Thus, EndoG promotes mitochondrial respiration by selectively regulating the production of mt-tRNA Thr in male mice.